2019
DOI: 10.24815/jdab.v6i1.10903
|View full text |Cite
|
Sign up to set email alerts
|

Tantangan Auditor Syariah: Cukupkah Hanya dengan Sertifikasi Akuntansi Syariah?

Abstract: The objective of this research is to propose the idea that a merely accounting certification is not sufficient for a profession of shariah auditor. Departing from this notion, the paper applied a library research combined with an interview method to explore further the issues. The result shows that the lack of educational institutions and certification for shariah auditor in Indonesia become the reasons why people are still doubting about auditor's competences. Shariah Accounting Certification conducted by Ika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
(7 reference statements)
0
3
0
6
Order By: Relevance
“…Meanwhile, the lack of institutions in the world of education and certification for a sharia auditor in Indonesia in the era of the Industrial Revolution 4.0, as it is now, makes customers still doubt the competence of sharia auditors in Indonesia, where the certification of sharia accounting is carried out by IAI (Indonesian accountants association). only engaged in accounting techniques, but in terms of sharia auditing competence in Indonesia is still minimal (Dewi & Sawarjuwono, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the lack of institutions in the world of education and certification for a sharia auditor in Indonesia in the era of the Industrial Revolution 4.0, as it is now, makes customers still doubt the competence of sharia auditors in Indonesia, where the certification of sharia accounting is carried out by IAI (Indonesian accountants association). only engaged in accounting techniques, but in terms of sharia auditing competence in Indonesia is still minimal (Dewi & Sawarjuwono, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the characteristics of the CFO / company leadership did not have a significant effect on the timeliness of financial reporting and audit quality did not moderate the effect of financial statement manipulation and the characteristics of the CFO. Research by (Dewi & Sawarjuwono, 2019) found that there is still a lack of institutions in the world of education and certification for a sharia auditor in Indonesia in the era of the Industrial Revolution 4.0 as it is currently making customers doubt the competence of sharia auditors in Indonesia, where accounting certification Sharia practices carried out by the IAI (Indonesian accountant association) are only involved in accounting techniques, but in terms of competence in sharia auditing in Indonesia, it is still minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Teknologi dapat mempercepat kinerja seorang akuntan, serta dapat menghindari terjadinya error. Seorang akuntan membutuhkan keterampilan dan pelatihan dalam penggunakan teknologi terbaru untuk kemudian lanjut mengikuti sertifikasi (Dewi & Sawarjuwono, 2019). Ada beberapa kemampun dasar yang perlu dipelajari oleh seorang akuntan yaitu analisis data, data science, computer science.…”
Section: Peran Akuntan Syariah Dalam Menghadapi Society 50 Pada Era Vucaunclassified
“…Motivation to learn accounting can be done by applying the principles of basic accounting calculations, namely addition, subtraction, multiplication and division (Dewi & Sawarjuwono, 2019). The enthusiasm to explore accounting since secondary schools (SMA or SMK for Indonesian) can arise from the information obtained about careers in the world of accounting which is at the wide range (Nurniah & Nasir, 2017).…”
Section: Motivation In Accountingmentioning
confidence: 99%